Analysis of volatile marker compounds in body fluid samples from patients with gastrointestinal disease - Fowler, Dawn P. (Cranfield University, 2010)
Causes of gastrointestinal diseases such as ulcerative colitis (UC) Crohn’s disease (CD) and irritable bowel syndrome (IBS) are not yet completely understood and clinical investigation for diagnosis is invasive, costly and time consuming. Disease may originate from the host or in combination with commensal enteric bacteria, notably sulphate reducing bacteria. Examination of volatile compounds from clinical samples may provide indicators and better understanding into aetiology of these conditions and provide biomarkers for individual disease.Cont/d.